RANCANG BANGUN MINIATUR TEMPAT PARKIR DENGAN METODE ELEKTRONIK PARKING PRICING (EPP) BERBASIS ARDUINO UNO - Raflianto, Gasa; Sasmoko, Priyo (Gema Teknologi, 2015)
Gasa Raflianto, Priyo Sasmoko, in this paper explain that design of miniature electronic methods parking place with parking pricing (EPP) based arduino uno created by looking at the problems that occur at this time, Berparkir is something that is often encountered in everyday dikehidupan. sometimes it is crucial to find the solution in order to provide convenience and comfort for the driver of the vehicle as well as the efficient use of parking space limitations. A lot of wasted time and sometimes quite a hassle just to queue entrance and exit of the parking lot during rush hour. Based on these problems, the authors provide a solution by designing a tool that can enable people to berparkir without having taken the trouble to enter and exit the parking lot without having to waste time and tenaga.Sistem is also supported by the Arduino Uno as the brain to process data from RFID, infrared is used to instruct the servo and servo motor is used as a parking portal. Keywords:, Servo, RFID, Infrared Sensor.ReferencesAnonim. Sensor. 5 agustus 2015. https://id.wikipedia.org/wiki/SensorIsyanto, Jazi Eko. 2014. Pengantar Elektronika dan Instrumentasi Pendekatan Project Arduino dan Android. Yogyakarta: ANDI.Koestoer, Raldi Artono.2004. Pengukuran Teknik. Jakarta: Departemen Teknik Mesin Fakultas Teknik Universitas Indonesia.Massimo dkk., Arduino/Genuino Uno, 29 juli 2015.Purnama , Agus, Kapasitor,  28 juli 2015Purnama , Agus, motor servo,  28 juli 2015Varlag,Zum, RFID, 28 juli 2015Van Vlack. Lawrench, Ilmu dan Teknologi Bahan, Erlangga, hal 186Zona elektro, Pulsa kendali motor servo,  28 juli 2015Zona elektro, Komponen led Inframerah, 27 juli 2015.